2016
DOI: 10.1589/jpts.28.1538
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic auditory stimulation using a portable smart device: short-term effects on gait in chronic hemiplegic stroke patients

Abstract: [Purpose] The effects of various rhythmic auditory stimulation tempos on stroke gait pattern changes when training patients with a smartphone-based rhythmic auditory stimulation application were investigated. [Subjects and Methods] Fifteen patients with chronic stroke were included. Cadence during comfortable walking was measured (baseline). After the baseline findings were recorded, rhythmic auditory stimulation with five different tempos (i.e., −10%, −5%, 0%, +5%, and +10% change from baseline) was randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…Immediate effects of RAS training with tempo changes were also found on gait kinematics (Cha et al, 2014) and in relation to the lesion site (Kobinata et al, 2016). Finally, there is growing support for the use of RAS in gait training during the chronic phase of stroke to improve walking speed and functional mobility (e.g., Shin et al, 2015; Ko et al, 2016; Wright et al, 2016, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Immediate effects of RAS training with tempo changes were also found on gait kinematics (Cha et al, 2014) and in relation to the lesion site (Kobinata et al, 2016). Finally, there is growing support for the use of RAS in gait training during the chronic phase of stroke to improve walking speed and functional mobility (e.g., Shin et al, 2015; Ko et al, 2016; Wright et al, 2016, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Due to technological and spatial limitations, fast walking for long distance in daily life is difficult to be observed by scientific equipment. In the literature, most of the gait experiments were done by walking on treadmills [ 5 , 7 , 8 , 10 ]. Actually, gait signals acquired on treadmills are quite different from the signals on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Their study indicated that music and metronome cues may not be used interchangeably, and the cue type and frequency (cadence) should be considered when evaluating effects of rhythmic auditory cues on gait. In [ 10 ], the gait pattern in various rhythmic auditory stimulation tempos was investigated in stroke patients. The results showed that as the tempo increased, the spatiotemporal gait parameters of the stroke patients changed significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhythmic-auditory stimulation (RAS) is defined as a therapeutic application of pulsed rhythmic or musical stimulation in order to improve gait or gait related aspects of movement ( 5 ). It has been demonstrated that SP are able to synchronize their gait pattern to auditory stimulation using music with an embedded metronome ( 6 8 ). This led to immediate improvements in stride time and stride length symmetry as well as weight bearing time on the paretic side, while EMG showed a more balanced muscular activation pattern between the paretic and non-paretic sides ( 6 ).…”
Section: Introductionmentioning
confidence: 99%